2022
DOI: 10.1111/nph.18217
|View full text |Cite
|
Sign up to set email alerts
|

OSCA1 is an osmotic specific sensor: a method to distinguish Ca2+‐mediated osmotic and ionic perception

Abstract: Summary Genetic mutants defective in stimulus‐induced Ca2+ increases have been gradually isolated, allowing the identification of cell‐surface sensors/receptors, such as the osmosensor OSCA1. However, determining the Ca2+‐signaling specificity to various stimuli in these mutants remains a challenge. For instance, less is known about the exact selectivity between osmotic and ionic stresses in the osca1 mutant. Here, we have developed a method to distinguish the osmotic and ionic effects by analyzing Ca2+ incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In Arabidopsis, Ca 2+ elevations in response to hyperosmotic stress depend on OSCA1, which operates as an osmosensor in the root and guard cell plasma membrane [ 52 , 53 ]. In addition, Ca 2+ channel-forming annexins activated by hydroxyl radicals may play a role under osmotic and salt stress conditions [ 54 ], a mechanism that has also been suggested for barley [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, Ca 2+ elevations in response to hyperosmotic stress depend on OSCA1, which operates as an osmosensor in the root and guard cell plasma membrane [ 52 , 53 ]. In addition, Ca 2+ channel-forming annexins activated by hydroxyl radicals may play a role under osmotic and salt stress conditions [ 54 ], a mechanism that has also been suggested for barley [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathway employing the Ca 2+ channel pattern along root cells, endoplasmic reticulum-localized type 2A Ca 2+ -ATPase (ECA1), and MIZU-KUSSEY1 (MIZ1), have been shown to play an important role in root hydrotropism in the model plant Arabidopsis [ 111 ], although the complete molecular mechanism, including the sensor, remains unclear. Part of the mechanism could be hyperosmolality-gated Ca 2+ -permeable ion channels such as OSCA1 that can modulate Ca 2+ concentration in response to osmotic stress [ 112 ] and distinguish between osmotic and ionic stress [ 113 ]. Recently, the role of plasma membrane-localized OSCA1.1 in root bending and hydrotropism has also been confirmed [ 114 ].…”
Section: Abiotic Stresses and Cropsmentioning
confidence: 99%
“…The osca1 mutant shows impaired Ca 2+ signaling in response to osmotic stress but not salt stress [16]. Recent mathematical fitting/modeling analysis in wild-type Arabidopsis and theosca1 mutant revealed that OSCA1 is responsible for the increase of [Ca 2+ ] cyt induced by osmotic stress rather than ionic stress [17].…”
Section: Osmotic Sensormentioning
confidence: 99%
“…Different from animals, plants might sense salt through a multicomponent ion channel complex rather than through simple ion channels. In addition, this ion channel complex might not be controlled directly by salt [17,24,27]. Identifying the salt sensor remains a problem that scientists are eager to solve.…”
Section: Ionic Sensormentioning
confidence: 99%